Internationalization of a Company's Activities as a Means of Survival and Growth in the Global Economic Crisis - Eugen BURDUŞ (Revista de Management Comparat International)
One of the explanations of developments favorable to companies or for their failures throughout the world lies in including the organization of activities outside the country of origin, the management practiced by headquarters, the parent company and its subsidiaries in the countries they were created and their conducting business. The relations between centralization and decentralization, between central unit and subsidiaries in different countries or cultures make a decisive influence on resources use, with strong impact over efficiency and competitiveness. This paper presents some considerations concerning the need of adoption, especially in a crisis, a model of the internationalization of a company's activities, corresponding to the basic activity and to the economic, social and cultural environment where intends to expand its activities.